Lovastatin Alleviates α-Synuclein Aggregation and Phosphorylation in Cellular Models of Synucleinopathy - Dai, Lijun; Wang, Jiannan; He, Mingyang; Xiong, Min; Tian, Ye; Liu, Chaoyang; Zhang, Zhentao (Frontiers in Molecular Neuroscience, 2021)
Parkinson's disease (PD) is one of the most common neurodegenerative diseases. Pathologically, it is characterized by the aberrant aggregation of α-synuclein (α-syn) in neurons. Previous clinical evidence shows that patients with hypercholesterolemia are at increased risk of PD, while lovastatin users are at a reduced risk. In this study, we aimed to investigate the effect of lovastatin on the aggregation and phosphorylation of α-syn. Our results demonstrated that α-syn preformed fibrils induced the phosphorylation and aggregation of α-syn in HEK293 cells stably transfected with α-syn-GFP and SH-SY5Y cells, and lovastatin attenuated α-syn phosphorylation and aggregation in a concentration-dependent manner. Moreover, lovastatin inhibited oxidative stress, histone acetylation, and the kinase activity of casein kinase 2. Collectively, our results revealed that lovastatin alleviates α-syn aggregation and phosphorylation in cellular models of synucleinopathy, and can be a potential therapeutic drug for PD.